Education on the Production of Fig Leaves Extract Hand Sanitizer in Cilayung Village, Jatinangor - Nyi Mekar Saptarini; Resmi Mustarichie; Diah Lia Aulifa; Rini Hendriani (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
Abstract. During the COVID-19 pandemic, people are advised to always wash their hands using soap and running water or hand sanitizer. Concerns about dangerous chemicals in hand sanitizers encouraged us to carry out community service in villages close to our campus, namely Cilayung Village, Jatinangor, West Java. In this activity, we used the fig plant, which was proven to have antibacterial activity. This community service aims to use fig leaf extract as an active ingredient in hand sanitizer. The method used is simple technology on a household scale: boiling fig leaves to obtain an extract, which is then formulated into a hand sanitizer. Before the activity, we optimized the formula of hand sanitizer from fig leaves. During community service, we provide education on fig leaves which have antibacterial activity, accompanied by making your own (do-it-yourself) hand sanitizer that can be used every day. The result, which is assessed through an interactive quiz, shows that education can increase participants’ knowledge regarding the use of fig leaves, and they can process fig leaves into hand sanitizer. The conclusion is that people know the benefits of fig leaves and how to process them into hand sanitizer.